2023
DOI: 10.3390/pathogens12020204
|View full text |Cite
|
Sign up to set email alerts
|

Taenia crassiceps Cysticercosis in a Wild Muskrat and a Domestic Dog in the Northeastern United States

Abstract: Taenia crassiceps is a parasite of wild canids and dogs that serve as definite hosts, harboring the adult cestode, whereas rodents are the intermediate hosts in which the metacestode/cysticercus/larval stage occurs. Fecal-oral transmission ensures the parasite’s lifecycle. At times, dogs and humans act as accidental intermediate hosts. Despite the public health concern this parasite warrants, its epidemiology remains unclear. In this report, we document the occurrence of metacestodes of T. crassiceps in a musk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Taenia crassiceps is a parasite of zoonotic significance, as humans may act as accidental intermediate hosts [14][15][16]. The article by Zhang et al [17] documents the occurrence of cysticercosis caused by T. crassiceps in a muskrat (Ondatra zibethicus) and in a domestic dog from the northeastern United States (New Jersey). The infection was identified via parasitological and histopathological examinations in both cases, while in the case of the muskrat, a molecular identification of the parasite species was also performed.…”
Section: Wildlifementioning
confidence: 99%
See 1 more Smart Citation
“…Taenia crassiceps is a parasite of zoonotic significance, as humans may act as accidental intermediate hosts [14][15][16]. The article by Zhang et al [17] documents the occurrence of cysticercosis caused by T. crassiceps in a muskrat (Ondatra zibethicus) and in a domestic dog from the northeastern United States (New Jersey). The infection was identified via parasitological and histopathological examinations in both cases, while in the case of the muskrat, a molecular identification of the parasite species was also performed.…”
Section: Wildlifementioning
confidence: 99%
“…The infection was identified via parasitological and histopathological examinations in both cases, while in the case of the muskrat, a molecular identification of the parasite species was also performed. Cysticercosis caused by T. crassiceps in dogs had already been described in the same area, but it was considered a rare disease; the first description of muskrat infection in the area, by Zhang et al [17], suggests that veterinarians and medical doctors should increase their awareness regarding this parasite in order to achieve timely diagnosis, interventions and surveillance, in relation to the "One Health" concept.…”
Section: Wildlifementioning
confidence: 99%
“…Natural infections with T. crassiceps have also been described in arctic foxes ( Vulpes lagopus ), sand foxes ( Vulpes ferrilata ), wolves ( Canis lupus ), golden jackals ( Canis aureus ), raccoons ( Procyon lotor ), raccoon dogs ( Nyctereutes procyonoides ), wild cats ( Felis silvestris ), stone martens ( Martes foina ), domestic dogs ( Canis lupus familiaris ), and cats ( Felis catus ) (reviewed in [ 17 ]). Although rodents and rabbits are primarily intermediate hosts, numerous other mammals, including humans, can also harbour the larval stage [ 6 , 17 , 18 , 19 ]. In intermediate hosts, upon ingestion of a taeniid egg, an oncosphere, also called a hexacanth embryo, hatches from the egg, penetrates the intestinal wall, and migrates through the bloodstream or lymph flow to the tissues or organs of predilection, such as the subcutis, muscles, and body cavities.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, severe cysticercosis can develop in intermediate hosts, leading to a fatal outcome. Several studies reported that carnivores such as dogs, cats, and foxes can also develop cysticercosis caused by C. longicollis , presuming that immunocompromised status was the main cause of disease occurrence [ 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%